2016
DOI: 10.1016/j.bandc.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Functional independence in resting-state connectivity facilitates higher-order cognition

Abstract: Growing evidence suggests that intrinsic functional connectivity (i.e. highly structured patterns of communication between brain regions during wakeful rest) may encode cognitive ability. However, the generalizability of these findings is limited by between-study differences in statistical methodology and cognitive domains evaluated. To address this barrier, we evaluated resting-state neural representations of multiple cognitive domains within a relatively large normative adult sample. Forty-four participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…Moreover, regions comprising these networks show anticorrelated task-induced activations that increase with increasingly demanding cognitive load ( Hampson et al, 2010 ; Persson et al, 2007 ; Douw et al, 2016 ; Leech et al, 2011 ; Grady et al, 2010 ; Hugdahl et al, 2019 ; Amer et al, 2016 ; Avelar-Pereira et al, 2017 ). Similar results are observed at rest, such that greater anticorrelation between task positive and negative networks is associated with improved cognitive control capacity measured outside of the scanner ( Keller et al, 2015 ; Kelly et al, 2008 ; Reineberg et al, 2018 ; Kim and Kang, 2018 ; James et al, 2016 ; Medaglia et al, 2018 ). Such anticorrelation suggests that when task positive networks are more active, e.g., during a cognitively demanding task, the task negative network is less active, and vice-versa.…”
supporting
confidence: 68%
“…Moreover, regions comprising these networks show anticorrelated task-induced activations that increase with increasingly demanding cognitive load ( Hampson et al, 2010 ; Persson et al, 2007 ; Douw et al, 2016 ; Leech et al, 2011 ; Grady et al, 2010 ; Hugdahl et al, 2019 ; Amer et al, 2016 ; Avelar-Pereira et al, 2017 ). Similar results are observed at rest, such that greater anticorrelation between task positive and negative networks is associated with improved cognitive control capacity measured outside of the scanner ( Keller et al, 2015 ; Kelly et al, 2008 ; Reineberg et al, 2018 ; Kim and Kang, 2018 ; James et al, 2016 ; Medaglia et al, 2018 ). Such anticorrelation suggests that when task positive networks are more active, e.g., during a cognitively demanding task, the task negative network is less active, and vice-versa.…”
supporting
confidence: 68%
“…In the study, it was reported that faster TMT-B performance (indexed by the completion time cost of TMT-B relative to the TMT-A) was associated with increased FC between bilateral intraparietal sulci and the remainder of the executive control network. More recently, a rs-FC study in a cohort of young, healthy adults extended these findings by highlighting the role of the FC between the left superior parietal lobule and right ventrolateral prefrontal cortex in mediating TMT switching performance ( James et al, 2016 ). In this study, the TMT variant of the D-KEFS ( Delis et al, 2001 ) was used to estimate the completion time increase for the letter-number switching condition (analogue of the TMT-B) relative to the number sequencing baseline condition (analogue of the TMT-A).…”
Section: Functional Neuroimaging Studies In Healthy Individualsmentioning
confidence: 86%
“…Resting-state fMRI studies of the TMT highlighted the importance of FC between the bilateral superior parietal cortex and prefrontal regions ( Seeley et al, 2007 , James et al, 2016 ) for adequate performance on the TMT-B ( Fig. 1 c).…”
Section: Neural Correlates Of the Tmt: Converging Evidence And Discrementioning
confidence: 99%
See 1 more Smart Citation
“…The number of studies comparing resting state fMRI (rsfMRI) activity and neuropsychological tests performance is sparse. A recent study in healthy volunteers (James et al, 2016 ) showed a significant effect of the TMT B performance (time to complete) to resting-state connectivity of two regions of interest (ROIs), the right VLPFC and left superior parietal lobule.…”
Section: Trail Making Test (Tmt)mentioning
confidence: 99%